Virgil on the nature of things : the Georgics, Lucretius, and the didactic tradition - Gale, Monica (Monica R.) (Cambridge University Press, 2000)
This book explores the relationship between the Georgics and earlier works in the didactic tradition. It is the first comprehensive study of Virgil's use of Lucretian themes, imagery, ideas and language; it also proposes a new reading of the poem as a whole.